Pengelolaan Sampah Di Lingkungan Rumah Tangga Demi Terwujudnya Kesehatan Keluarga - Nora Amelia Novitrie; Am Maisarah Disrinama; Ulvi Pri Astuti; Devina Puspita Sari; Ika Erawati; Yesica Novrita Devi; Mey Rohma Dhani; Renanda Nia; Aulia Nadia Rachmat (Universitas Nahdlatul Ulama Sidoarjo, 2025)
The composition of waste generated from human activities is 60-70% organic waste, and the remainder is non-organic waste (30-40%). Of this non-organic waste, plastic waste makes up the second largest portion, at 14%. The large percentage of household waste represents both a problem and an opportunity to address the waste problem at its source. This can be achieved by involving and educating housewives who come into direct contact with household waste. Housewives should be educated on the importance of managing waste from its source, using the 3R principle (Reduce, Reuse, Recycle), classifying the types of plastic waste, and handling them appropriately. Educated housewives are expected to become ambassadors who will spread their understanding of the importance of changing the public's mindset regarding plastic waste management.